Sistem Informasi Pariwisata Alam di Kabupaten Labuhanbatu Berbasis Web - Purba, Cinrewina; Nasution, Marnis; Muti Ah, Rahma (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Indonesia is a country rich in natural resources. nature tourism has a unique and interesting natural wealth as the main attraction for people who like to visit nature. Saving the environment and biodiversity becomes very important, and nature tourism can be a means to increase public awareness and involvement in Nature Conservation. Each of these tours has its own beauty and characteristics. Tourism is one of the sectors that has the opportunity to become the largest foreign exchange contributor in Indonesia, tourism growth in indonesia was recorded at 7.2 percent per year, higher than the average world tourism growth of only 4.7 percent. Labuhanbatu Regency is one of the regions of North Sumatra that has a good tourism sector.but in the dissemination of information about tourism is still a manual, among others, the provision of brochures, posters, pamphlets to tourists who visit. The Office of Youth, Sports, Culture and tourism does have a website about natural tourism in Labuhanbatu but its webiste can not be opened, and the automatic development of natural tourism can not be updated to the website. At the time of the tour, the tourists also must be really tired on the way and want to stay at the tourist attractions. To ensure the presence or absence of lodging in these tourist attractions,it is very necessary for the website to more easily find out information about natural attractions in Labuhanbatu Regency.